1999
DOI: 10.1046/j.1469-0705.1999.14030215.x
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of interrupted inferior vena cava as an isolated finding: a benign vascular malformation

Abstract: We report two cases of interrupted inferior vena cava with azygous continuation diagnosed as an isolated finding during routine prenatal scans. Visualization of the venous vasculature of the abdomen and thorax in the mid-sagittal plane failed to visualize the segment of the inferior vena cava between the kidneys and the liver. A vessel with venous flow was observed parallel, adjacent and posterior to the aorta between the kidney and the right atrium. This blood vessel connected with the superior vena cava. Axi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
19
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 12 publications
(13 reference statements)
3
19
0
Order By: Relevance
“…Van Praagh et al [7] reported an interrupted IVC in 39 of 46 (85%) postmortem cases of visceral heterotaxy with polysplenia. But, isolated ınterrupted IVC with azygos continuation has been rarely described [8][9][10], comparable with the case we report.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Van Praagh et al [7] reported an interrupted IVC in 39 of 46 (85%) postmortem cases of visceral heterotaxy with polysplenia. But, isolated ınterrupted IVC with azygos continuation has been rarely described [8][9][10], comparable with the case we report.…”
Section: Discussionsupporting
confidence: 90%
“…This might be a second potential pitfall in the diagnosis of an azygos continuation. This problem may be resolved by late contrast-enhanced scan on CT examination or by use of magnetic resonance imaging [9].…”
Section: Discussionmentioning
confidence: 99%
“…Although the majority of cases with IVC interruption are associated with visceral heterotaxy, especially in LAI, it can occur as an isolated finding, which is very rare [22]. When IVC is absent by ultrasonography, examiners should keep in mind the possibility of associated cardiac anomalies, and if no abnormalities are detected, the prognosis is excellent unlike that associated with LAI [23].…”
Section: Discussionmentioning
confidence: 99%
“…Persistent left superior vena cava to the coronary sinus is a more common venous anomaly that has been recognized in the fetal life, both with and without cardiosplenic syndrome [10]. The occurrence of congenitally interrupted inferior vena cava without heterotaxia syndrome is extremely rare [11][12][13][14][15], and the frequency of associated additional vascular and cardiac anomalies in these patients is not well known [11]. Failure to recognize this anomaly can result in various problems during invasive medical or surgical procedures [16,17].…”
Section: Discussionmentioning
confidence: 99%